2009
DOI: 10.1007/s00125-009-1276-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of enteroviral capsid protein vp1 immunostaining in pancreatic islets in human type 1 diabetes

Abstract: Aims/hypothesis Evidence that the beta cells of human patients with type 1 diabetes can be infected with enterovirus is accumulating, but it remains unclear whether such infections occur at high frequency and are important in the disease process. We have now assessed the prevalence of enteroviral capsid protein vp1 (vp1) staining in a large cohort of autopsy pancreases of recent-onset type 1 diabetic patients and a range of controls. Methods Serial sections of paraffin-embedded pancreatic autopsy samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
346
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(375 citation statements)
references
References 38 publications
24
346
2
3
Order By: Relevance
“…3 The presence of EV protein in the pancreas of T1D patients has been observed. 4 Prospective studies confirmed the link between EV and the development of pancreas islet autoimmunity. 5 Moreover, experimental studies, in vitro and in vivo animal models, revealed that CV-B4 may be involved in the pathogenesis of T1D through several mechanisms.…”
Section: Introductionmentioning
confidence: 87%
“…3 The presence of EV protein in the pancreas of T1D patients has been observed. 4 Prospective studies confirmed the link between EV and the development of pancreas islet autoimmunity. 5 Moreover, experimental studies, in vitro and in vivo animal models, revealed that CV-B4 may be involved in the pathogenesis of T1D through several mechanisms.…”
Section: Introductionmentioning
confidence: 87%
“…We focused on enteroviruses and coxsackie viruses as they are suspected to have a role in T1D development. [13][14][15] Monozygotic status of the quadruplets was confirmed by testing 14 different short tandem repeat polymorphisms using Aneufast multiplex QF-PCR kit (molGENTIX, S.L., Barcelona, Spain), recommended by CODIS (Combined DNA Index System). 20 …”
Section: Hla Typing Confirmation Of Monozygosity and Viral Studiesmentioning
confidence: 99%
“…[9][10][11][12] Notably, and in this context, several recently published findings suggest a strong link between T1D and enteroviral infections. [13][14][15] To prevent the clinical onset of T1D, immuno-intervention should be undertaken in the clinically silent pre-diabetic phase. However, it is difficult to identify suitable candidates for such interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have suggested that infections with enteroviruses, in particular those of the coxsackie B virus (CVB) serotypes, may be linked to islet autoimmunity and development of type 1 diabetes [1][2][3][4][5]. Other observations suggesting that infections with these viruses have a causative role in diabetes development come from studies that found enteroviruses more frequently in pancreases [6][7][8] and, in some studies, also gut biopsies [9][10][11], from patients with type 1 diabetes compared with healthy controls. Some enteroviruses, including the CVBs, are pancreatropic and can infect human beta cells in vitro, often with a detrimental outcome (e.g.…”
Section: Introductionmentioning
confidence: 99%